Timing of Paleoearthquakes and Seismic Hazard of the Zhuozishan West Piedmont Fault in the Northwestern Ordos Block - Liu, Xingwang; Gao, Zemin; Lei, Qiyun; Shao, Yanxiu; Yao, Yunsheng (Frontiers in Earth Science, 2022)
The Zhuozishan West Piedmont Fault (ZWPF) is an active normal fault in the northwestern corner of the Ordos Block. Studying the recurrence characteristics of paleoearthquakes is useful for understanding the regional seismic hazard potential. In this study, paleoseismic trench and optically stimulated luminescence (OSL) dating methods are used to determine the temporal sequence of paleoearthquakes. Severn earthquakes were constrained to be E7 (73.4 ± 12.9 ka to 75.3 ± 10.6 ka), E6, (63.7 ± 7.4 ka to 64.4 ± 8.2 ka), E5 (53.2 ± 7.0 ka to 58.7 ± 6.5 ka), E4 (42.6 ± 6.3 ka to 47.7 ± 5.8 ka), E3 (31.0 to 3.4 ka to 31.3 ± 3.4 ka), E2 (26.1 ± 2.7 ka to 28.1 ± 3.8 ka) and E1 (15.8 ± 1.9 ka to 20.2 ± 2.6 ka). The recurrence interval of strong earthquakes in the ZWPF is roughly constrained to be 8.1-14 ka, with magnitudes of Mw 7.0–7.4 that ruptured the entire fault. Based on the timing of the latest earthquake event, the elapsed time approached or exceeded the recurrence interval revealed from paleoearthquakes. Hence, we suggest that the northwestern corner of the Ordos Block has a significantly high seismic hazard potential and that the occurrence of a strong earthquake should not be underestimated.